The Relevance of Double Effect Doctrine in The Perspective of Criminal Law Causality Doctrine: A Rebuttal to The Concept Of Conditio Sine Qua Non - Nafis Dwi Kartiko (Activa Yuris: Jurnal Hukum, 2024)
This research explores and analyzes how the doctrine of causality, particularly the concept of Conditio Sine Qua Non, and the doctrine of double effect interact and influence the determination of responsibility in criminal law. Using the normative-dogmatic research method, this study systematically analyzes applicable legal rules without empirical data, emphasizing the qualitative application of legal and philosophical principles. The research uses a literature review as the primary data collection tool, examining legal philosophy books, academic journals, and professional publications to draw relevant conclusions. The results indicate that Conditio Sine Qua Non, which focuses on objective causation, needs to be revised for cases involving complex ethical considerations. In contrast, the double effect doctrine introduces an ethical dimension to causality judgments, justifying actions that produce unintended but unavoidable adverse consequences as a side effect of a good goal. The findings suggest that an integrative approach combining both doctrines may lead to a more balanced and comprehensive understanding of criminal liability. This research aims to enrich the academic discourse on causality in criminal law by introducing ethical considerations as part of causal analysis. It offers a new perspective in dealing with criminal cases involving complicated morality and consequences, challenging the existing limitations of causal interpretation. Nevertheless, this study has limitations in terms of its scope of practical application and the need for empirical verification, signaling the need for further research that can evaluate and validate these findings in actual legal practice.